Points of view an anthology of short stories - McElheny, Kenneth R. editor; Moffett, James (New York New American Library, 1995)
Collection offers fresh perspective on short story form concerning narration.
First published in 1966.
Previous edition entered under James Moffett.
KSSP-2894 donated by Prof. Michael L. Tan, Chancellor University of the Philippines Diliman.
Keywords: Short stories